Role of nutrition-sensitive agriculture in enhancing sustainable humanitarian assistance: Evidence from orange-fleshed sweetpotato interventions in Kenya - Mulwa, C.K.; Grant, F.; Gatto, M.; Moyo, M.; Amunga, D.; Kwikiriza, N.; Malit, J.; Okello, J.J.; Maru, J.; Campos, Hugo; Heck, S. (Elsevier, 2025)
The increasing frequency of climate-related shocks in arid and semi-arid regions has subjected local populations to cyclical livelihood disruptions and poverty traps. Humanitarian assistance is key to sustainable livelihoods in such regions, but this has largely been in the form of emergency aid. Sustainability concerns and public f iscal burden have necessitated a shift towards resilience building. Such interventions include biofortification, an important nutrition-sensitive agricultural approach that can sustainably improve food and nutrition security among vulnerable populations. However, there is limited evidence of success and lessons for scaling this approach. Using a sample of 636 households drawn from three arid and semi-arid counties in Kenya, this study uses a doubly robust estimator and non-parametric methods to investigate the effect of promoting vitamin-A-biofortified sweet potato as a nutrition-sensitive, climate-smart agricultural intervention to improve nutritional outcomes in humanitarian settings. We find that interventions combining demand-creation strategies and access to biofortified planting material significantly enhance nutrition knowledge and household nutrition indicators such as dietary diversity and food security. Individual interventions that either create demand or provide access to planting material enhance nutrition awareness but do not lead to primary nutrition outcomes such as dietary diversity. Lastly, enhancing access to planting material leads to higher nutritional outcomes compared to demand-creation strategies carried out in isolation.